QTLs for anaerobic germination of rice - CGIAR Research Program on Rice (2020)
QTL were identified, the donor BJ1 was validated as a source for anaerobic germination (it was previously identified by genome-wide association study); QTL and donor are available to breeders (next users) for variety development